Characterization of Bone Marrow pO2 by Two-photon Phosphorescence Quenching Method. - Spencer, Joel. (2017)
Abstract: Hematopoiesis is the process by which all the variety of red and white blood cells and platelets originate from primitive hematopoietic stem cells (HSCs) and their committed progenitors. In adults, hematopoiesis occurs primarily in the bone marrow (BM) whereby primitive HSCs divide giving rise to progenitor cells that can proliferate and differentiate into all the lineages of blood cells. HSCs reside in specialize BM compartments called `niches' where they are retained in a quiescent state. HSC maintenance and proliferation is dependent on intrinsic factors and extrinsic cues such as soluble molecules secreted by supporting cells such as osteoblastic, endothelial, and perivascular cells. Spontaneous failure along any point in the hematopoietic cascade can lead to dysfunction of the red or white blood cell lineages and eventually to hematopoietic disorders such as leukemia and lymphoma. Many hematopoietic disorders do not have effective treatments and therefore have very poor clinical outcomes. Understanding the function and interaction of environmental and cellular cues involved in HSCs maintenance and proliferation may reveal new targets for therapy and eventually lead to better clinical outcomes for hematopoietic disorders. One of the environmental cues thought to play a major role in hematopoiesis is molecular oxygen. The goal of this thesis was to build an intravital imaging/oxygen sensing system capable of reliably measuring the partial pressure of oxygen (pO2) in vivo with high spatial resolution and to use this tool to characterize BM vascular and extravascular pO2 in living mice. We successfully integrated a two-photon phosphorescence lifetime pO2 measurement technique with two-photon intravital imaging using one laser source based upon polarization optics. We demonstrated that we could routinely image the calvarial BM and measure pO2 in the vascular and extravascular spaces in live animals. We identified the normal range of BM vascular pO2 and found that the BM vasculature is hypoxic compared to other vascular beds. Furthermore, we found that the sinusoidal region of the BM was the most hypoxic, an important finding supporting the theory that the perisinusoidal region is the location of a hypoxic HSC niche. However, despite the fact that the blood vessels near the bone surface (endosteum) are the most oxygenated, the endosteal interstitial zone (<20 µm from the bone surface) also appears hypoxic, leaving open the possibility of the existence of a hypoxic osteoblastic HSC niche. We performed some preliminary studies using clinically relevant hematopoietic stem and progenitor cell (HSPC) transplantation models and found that in our hands, the HSPCs do not home to the lowest oxygen tension locations of the BM in the timeframe we observed. This is important for understanding how HSPCs repopulate the BM after radiation or chemotherapies. Manipulation of the pO2 in the BM before and after transplantation may have a therapeutic effect and increase the homing and engraftment ability of HSPCs.; Thesis (Ph.D.)--Tufts University, 2012.; Submitted to the Dept. of Biomedical Engineering.; Advisors: Mark Cronin-Golomb, and Charles Lin.; Committee: Irene Georgakoudi, and Daniel Jay.; Keywords: Biomedical engineering, Optics, and Biology.